Development of newsgroup server using Linux base operating system - 419224 Kamaru Adzha Kadiran (Skudai: Universiti Teknologi Malaysia, 2003)
Project Paper (Sarjana Muda Kejuruteraan (Elektrik-Telekomunikasi)) - Universiti Teknologi Malaysia, 2003